Not fot Profit: Why Democracy Needs the Humanities. Princeton University Press, 2010. (The public square book series) ISBN 978-0-691-14064-3 - Faversani, Fábio (Revista Archai, 2012)
Not fot Profit: Why Democracy Needs the Humanities. Princeton University Press, 2010. (The public square book series).